Effect of Carboxymethyl Chitin on Capsule Formation around Silicone Implants: An In Vivo and In Vitro Study. Issue 4 (27th July 2022) - Li, Shasha; Ren, Liwen; Jia, Di; Yang, Dan; Hao, Lijun
Abstract : Background: Capsular contracture is a serious complication that occurs after augmentation mammaplasty. The authors previously identified that carboxymethyl chitin had an inhibitory effect on capsule formation. This study was performed to elucidate the possible molecular mechanisms through which carboxymethyl chitin inhibits the formation of a capsule around silicone implants. Methods: In this study, the authors cultured human dermal fibroblasts and treated them with carboxymethyl chitin in vitro. The difference in proliferation between treated and untreated cells was analyzed through the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay. Protein levels of transforming growth factor beta-1 and alpha smooth muscle actin (α-SMA) were examined by Western blot analysis. Expression levels of type I and type III collagen were checked by enzyme-linked immunosorbent assay. In vivo, silicone implants were placed under the pectoralis muscle in 12 female rabbits. The thickness of the capsule was measured by histologic analysis, and the effect of carboxymethyl chitin on α-SMA, collagen type I and III expression levels was evaluated by real-time polymerase chain reaction analysis, enzyme-linked immunosorbent assay, Western blot, and immunofluorescence analysis. Results: In the in vitro study, we confirmed that carboxymethyl chitin inhibited the proliferation of fibroblasts. The protein expression levels of collagen type I, transforming growth factor beta-1, and α-SMA were inhibited by carboxymethyl chitin treatment. In vivo, carboxymethyl chitin treatment reduced capsular thickness and the expression of α-SMA and collagen types I and III in capsules around silicone implants. Conclusion: The authors' results showed that carboxymethyl chitin could influence capsule formation around silicone implants by inhibiting the fibroblast activity, interrupting fibroblast-to-myofibroblast differentiation, and decreasing collagen synthesis. Clinical Relevance Statement: Carboxymethyl chitin influence capsule formation around silicone implants. Although more clinical studies are needed to verify the effect of carboxymethyl chitin on capsular contracture, the authors believe that it will play an effective role in the clinical application of reducing the occurrence of capsular contracture.